Explaining the Last Consumption Boom-Bust Cycle in Ireland : The Role of News and Noise Shocks - Diaz Sanchez, Jose Luis (World Bank, Washington, DC, 2013)
The objective of the paper is to explain the last boom and bust in consumption in Ireland by the failure of consumers to correctly distinguish permanent changes in productivity from temporary changes. It uses a business cycle model, where agents update their beliefs about long-run productivity using information -that they receive continuously- about the future state of the economy. The analysis finds that a large and prolonged disconnect between consumption and long-run productivity occurred in the years leading to the economic crisis, which led to -- over-consumption -- for several quarters. A strong downward adjustment in 2008 followed when Irish consumers finally realized their mistake.